2016
DOI: 10.1002/cam4.668
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant horseradish peroxidase variants for targeted cancer treatment

Abstract: Cancer is a major cause of death. Common chemo‐ and radiation‐therapies damage healthy tissue and cause painful side effects. The enzyme horseradish peroxidase (HRP) has been shown to activate the plant hormone indole‐3‐acetic acid (IAA) to a powerful anticancer agent in in vitro studies, but gene directed enzyme prodrug therapy (GDEPT) studies showed ambivalent results. Thus, HRP/IAA in antibody directed enzyme prodrug therapy (ADEPT) was investigated as an alternative. However, this approach has not been int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…HRP was used for the investigation of inhibitor activity of anti-inflammatory drugs [15]. In other studies it has been found that better understanding the role of HRP and other peroxidases in this process could lead to a new targeted cancer therapy [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…HRP was used for the investigation of inhibitor activity of anti-inflammatory drugs [15]. In other studies it has been found that better understanding the role of HRP and other peroxidases in this process could lead to a new targeted cancer therapy [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the interactions with herbal products (9.1% of patients) in this study, the pharmacist advised not to use these products, since literature do not provide any robust evidence to indicate the mechanism and management of those interactions. [23][24][25] A combination of chemotherapeutics and use of other medications for comorbid conditions poses a significant risk for drug interactions in cancer treatment. A broad-spectrum of adverse effects of chemotherapeutics along with potential drug interactions may lead to increased toxicity and discontinuation of effective treatments in patients.…”
Section: Discussionmentioning
confidence: 99%
“…[12c] Nevertheless, due to the commonly low catalytic activity and stabilityo ft he activating enzymes required for EPT,v arious approaches, such as antibody-directed enzymep rodrug therapy (ADEPT), gene-directed enzyme-prodrug therapy (GDEPT), ands ubstrate-mediated enzymep rodrug therapy (SMEPT), have been developed to maintain the activity of the enzymes whilew orking in vivo. [33] In recent years, the introduction of therapeutic nanoreactors into EPT for cancer therapyw hich involves the immobilization of activating agentsi nto the matrices of synthetic nanoplatforms that can convert less or no-toxic prodrugs in situ into parentt oxic drugs, indicated great potentials over the traditional approaches in EPT,s uch as ADEPT or GDEPTwhich often suffer from the reduced catalytic activity,i mmunogenicity,a nd lack of efficiency for localized delivery duringt reatment. [10a, 31a] Amongt he unique advantages of using therapeutic nanoreactors in EPT for cancer therapy are:…”
Section: Cancer Treatment Strategies Based On Therapeuticn Anoreactormentioning
confidence: 99%